The solution of the inverse problem of lateral logging sounding in a terrigenous section - Myrontsov, M.L. (Reports of the National Academy of Sciences of Ukraine, 2020)
Using the example of lateral logging sounding, the possibility of assessing the influence of the adjacent beds and boundary effects on the real vertical resolution of the inverse problem is shown. It is shown how it is possible to improve this ability using a new approach to solving the inverse problem, which allows one to account for the quantitative contribution of the measurement of each probe to the final result. An example of such solution to the inverse problem of the “BKZ+BK” complex for a real well material in a terrigenous section is given. The following conclusions are made: for the correct use of the algorithm for solving the inverse problem, it is necessary to have an estimate of the vertical resolution of the electrometry method as a whole; a real assessment of the influence of boundary effects on the measurement of the apparent resistance of the probes of the complex allows us to evaluate the effectiveness of the method; the use of the proposed residual functional allows us to change the effect of probes of different lengths on the final result and thereby allows us to achieve a satisfactory accuracy even when studying the geoelectric parameters of formations whose power is less than the length of the largest probes of the electrometric complex. The results of the work were introduced into the production of a number of commercial geophysical organizations.